Qi, Yin, and Yang: Traditional Medicine Concepts of Acupuncture - Kinaryosih, Lintang; Farahan, Farisha Jasmine (Confucius Institute Universitas Sebelas Maret, 2023)
Acupuncture is a traditional treatment from China with historical roots going back centuries. It uses the method of fine needles inserted into the skin at acupoints located along the body's meridians. The main concepts that govern this treatment are Yin and Yang, as well as the flow of vital energy known as Qi. The acupuncture treatment method was first discovered in China in ancient times and has been continuously developed. Today, acupuncture has become one of the standard therapies in China, along with herbs and massage techniques. Acupuncture treatment has preventive and curative purposes and is considered more economical and practical in the healthcare system. The concept of Yin and Yang is essential in acupuncture treatment. It reflects the balance and duality of the human body and nature. Acupuncture points are considered to have Yin or Yang properties, and needles on these points aim to restore the balance of energy in the body. In addition, acupuncture treatment also aims to optimize the flow of Qi, the vital energy that flows throughout the body. When the flow of Qi is obstructed or unbalanced, this can lead to health problems. Acupuncture today is still beneficial as an adjunctive treatment method for pain, primarily when conventional medicine does not provide adequate results. This research aims to analyze how Qi, Yin, and Yang affect the healing process in the human body. In this research, the literature study method is used to explore Qi, Yin, and Yang in the context of acupuncture treatment. The results of this research help us better understand how the concepts of Yin, Yang, and Qi are applied in acupuncture treatment and how they work in the human body.